(untitled) (Research, Society and Development, 2023)
Stroke is one of the pathologies with the highest prevalence of deaths in Brazil, also standing out as a substantial cause of disability in the world. In this sense, clinical epidemiological knowledge of stroke is fundamental, in addition to its implications in scientific and public health scenarios. This study aims to analyze the clinical and epidemiological profile of cases of stroke in the State of Piauí, from 2011 to 2021. This is an epidemiological, documentary and quantitative research of a descriptive and retrospective nature, where the data collection scenario was the DATASUS database. The following variables were selected: sociodemographic (sex, age, race), character of care and mortality rate. In the evaluated period, the number of hospitalizations for stroke in the state of Piauí was 29,979 cases. With a higher occurrence in the age group from 70 to 79 years old, with 7,982 cases (26.62%), and a higher prevalence in males, 15,485 (51.65%) affected men. Most cases were urgent, with 29,863 cases (99.62%), and individuals of unknown race (49.19%). The capital of Teresina had the highest number of hospitalizations for stroke, about 12,339 cases. The stroke mortality rate was higher in 2015, around 17.81%. In the present study, it was possible to analyze that hospitalization rates for stroke have been decreasing over the years in the state of Piauí, as well as the mortality rate, however, there is a need to implement more strategies to promote health and prevent the occurrence of stroke.